EFFECTIVITY OF ZEOLITE ADDITION INTO RATION TO QUAIL PERFORMANCE OF 7- 14 WEEK - Riyanti, Riyanti; Kurtini, Tintin (Jurnal Zeolit Indonesia, 2007)
The aim of this experiment was to find the effect of supplementation of zeolit and was to find the optimum level of zeolit in rations on quail performance. This experiment used 80 female Coturnix coturnix japonica of five weeks old with average body weight 145,44 Â± 6,72 g (cv 4,62%). The data were analysed using Completely Randomized Design and polinomial ortogonal test. The treatments was divided to four supplementation zeolit rations treatment (0%,2%,4%,6%). Each treatment had five replication and each replication used four quails. Results of this study indicated that supplementation of zeolit (0 - 6%) in rations gave not significantly different (P â¥ 0,05) to feed consumption but gave significantly different (P < 0,05) to hen day egg production (Å¶ = 46,48 + 4,86X â 1,09 X2 ; 0â¤ X â¤6 ; R2 = 0,90) and significnatly different (P < 0,05) to feed convertion (Å¶= 4,85-0,44 + 0,10X 2 ; 0â¤Xâ¤6;R2 = 0,97). Level supplementation zeolit 2,22% was optimum to hen day egg production (51,86%) and level supplementation zeolit 2,09% was optimum to feed convertion (4,39).